Analysis of Users’ Requirements for Public Waste Management Services Using Fuzzy Inference - Cárdenas-Cuervo, Ricardo Andrés; Serna-Uran, Conrado Augusto; Gomez-Marin, Cristian Giovanny (Institute of Automation and Computer Science, Brno University of Technology, 2023)
Municipalities play a key role in public waste management ensuring effective and efficient service performance. In Colombia, the public utilities sector has undergone significant changes since decentralization and the entry of private companies into the sector. In this study, our purpose is to analyze user perceptions and their willingness to pay for additional services regarding waste management. By using data analysis methods and a Mamdani fuzzy inference system, we were able to identify users’ service requirements and expected quality. According to the results of our analysis, a combination of minimum coverage and low frequency resulted in a tariff increase of 7.05%. Furthermore, we recommend expanding the model to include other waste management services, such as solid waste collection, as well as to consider environmental aspects and sustainable practices.
Keywords: Waste Management; Public Service; Service Requirements; Fuzzy Inference; Tariff; User Perceptions